2004
DOI: 10.1016/j.cellbi.2004.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Tra2βl regulates P19 neuronal differentiation and the splicing of FGF‐2R and GluR‐B minigenes

Abstract: The present study demonstrates that the expression of Tra2beta1 (Transformer 2-beta1) proteins, an SR (serine/arginine rich) protein, is developmentally up-regulated in a neural-specific pattern. The up-regulation is also observed in RA (retinoic acid) induced neural differentiation of P19 cells. Tra2betal proteins are located in the nuclei of P19 cells, which are consistent with its functional site as an SR protein. The over-expression of Tra2betal proteins promotes RA induced neuronal differentiation of P19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…P19 is a teratocarcinoma-derived pluripotent stem cell line that can give rise to all three germ layers in mice (23). Undifferentiated P19 EC cells in culture can be induced by RA to differentiate to neuronal and glial cells (24,25) or by DMSO to cardiac and skeletal muscles (26). Treatment of P19 EC cells with RA for up to 4 days induces non-adhering aggregates called EBs which resemble the inner cell mass of embryos (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…P19 is a teratocarcinoma-derived pluripotent stem cell line that can give rise to all three germ layers in mice (23). Undifferentiated P19 EC cells in culture can be induced by RA to differentiate to neuronal and glial cells (24,25) or by DMSO to cardiac and skeletal muscles (26). Treatment of P19 EC cells with RA for up to 4 days induces non-adhering aggregates called EBs which resemble the inner cell mass of embryos (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…The transcript variants spliced from the minigenes are expected to be Flop (612 bp) and Flip (612 bp), respectively, in neurons. But, in cultured cells, the minigenes are expected to generate Flop and truncated (500 bp) transcript isoforms [8]. The truncated GluR-B transcript contains neither Flip nor Flop exon, as illustrated in Fig.…”
Section: Znf265-1 Regulates the Splicing Of Glur-b And Smn2 Minigenesmentioning
confidence: 99%
“…The Flop and truncated isoforms from the GluR-B minigene, as indicated in Fig. 4A, were identified using enzymatic digestion of the transcripts as described previously (8). The in vivo splicing analysis showed that overexpression of ZNF265-1 significantly decreased the ratio of Flop to truncated isoforms (Fig.…”
Section: Znf265-1 Regulates the Splicing Of Glur-b And Smn2 Minigenesmentioning
confidence: 99%
See 2 more Smart Citations